Oral health in patients on inhaled corticosteroid treatment - KURU, LEYLA (BLACKWELL PUBLISHING, 2005)
Objective: The aim of this study was to investigate the effects of long-term inhaled corticosteroids on bone mineral density (BMD) of the mandible in relation with the tooth loss. Design: Cross sectional analytic study. Subjects and Methods: Patients (n=30) with chronic obstructive pulmonary disease under inhaled corticosteroid therapy for at least 1 year were compared with sex- and age-matched healthy controls (n=30). BMD of the mandible was measured by dual-energy X-ray absorptiometry. The clinical examination included recording the number of teeth present together with periodontal condition. Levels of serum osteocalcin, alkaline phosphatase, calcium, phosphorus and cortisol were also assessed. Results: BMD of the mandible in patients on corticosteroid treatment was significantly lower than that in the control group (P=0.001). Patients under treatment had more missing teeth than the control group but the difference did not reach statistical significance. The two groups exhibited similar clinical parameters of periodontal condition. Significantly lower levels of osteocalcin (P<0.0001), calcium (P=0.004) and cortisol (P=0.03) were observed in the patients on corticosteroid treatment. Conclusion: Long-term use of inhaled corticosteroids may impair bone metabolism and lead to a marked decrease in the mandibular BMD.
Keywords: corticosteroids; bone mineral density; mandible; periodontitis; tooth loss; BONE-MINERAL DENSITY; PERIODONTAL-DISEASE; MANDIBULAR BONE; TOOTH LOSS; INDUCED OSTEOPOROSIS; THERAPY; WOMEN; ASSOCIATIONS; METABOLISM; CALCIUM